New Attributions to Sales Performance in a Highly Spiritual Market: Individuals’ Spirituality and Family Support - Franklin, Drew; Herjanto, Halimin (Indonesian Management and Accounting Research, 2026)
Salespeople play a critical role in determining the success of sales organizations through their performance. However, existing research has predominantly focused on Western contexts, with limited attention to highly spiritual markets where religiosity significantly influences personal and professional life. This study aims to examine the factors affecting salespeople’s performance within such a context. Adopting a qualitative approach, this study utilizes thematic analysis of semi-structured interviews with 24 high-performing life insurance salespeople in Indonesia. The findings identify four key categories influencing sales performance: salesperson, organization, buyer, and competitor. Among these, the salesperson category emerges as the most dominant. Notably, spirituality and family support are identified as two important and previously underexplored factors within this category. These findings contribute to the literature by reinforcing the central role of individual-level factors in driving sales performance while extending the discussion to include spiritual and familial dimensions. The results suggest that sales organizations should not only focus on developing selling skills and providing organizational support but also consider the internal values and personal well-being of salespeople. Encouraging alignment between work, personal beliefs, and family support may enhance sustainable sales performance, particularly in highly spiritual markets.